2010
DOI: 10.1080/09296170903395924
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Methods for Attributing Literary Works when Solving the “Corneille–Molière” Problem*

Abstract: This research work focuses on developing a linguistic approach in the field of attribution of literary works using the material of plays written in verse for which Molie`re is thought to be the author. In this research work, a solution of the problem ''Corneille-Molie`re'' is suggested by using methods of mathematical modelling and quantitative description of individual author styles on a syntactic level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The notion of distance separating two textual entities is difficult to handle, as it is first and foremost a metaphor. A simple solution is to compute it with the classical Euclidean distance ( 5 , 15 ). Yet, recent papers have advocated that the choice of the distance measure was a crucial problem in authorship attribution, which could markedly affect performance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The notion of distance separating two textual entities is difficult to handle, as it is first and foremost a metaphor. A simple solution is to compute it with the classical Euclidean distance ( 5 , 15 ). Yet, recent papers have advocated that the choice of the distance measure was a crucial problem in authorship attribution, which could markedly affect performance.…”
Section: Methodsmentioning
confidence: 99%
“…The lack of selection or treatment on the texts is hard to defend. Marusenko and Rodionova ( 15 ) tried to attribute 13 comedies in verse signed by Molière. These plays are compared to two sets of comedies in verse, one by P. Quinault and the other by P. Corneille, according to five grammatical criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Mendenhall proposed a method to analyze a composition by forming a "word spectrum," or "characteristic curve," which represents an arrangement of words according to their length and the relative frequency of their occurrence. Furthermore, Labbé, Cyril and Labbé, Dominique [48] and Marusenko and Rodionova [49] used a combination of stylistic and statistical methods to solve the authorship attribution and identification problem for the works of Moliere and Corneille. This problem was solved using mathematical modeling methods, and quantitative descriptions of individual author styles on a syntactic level.…”
Section: Statistical Modelsmentioning
confidence: 99%
“…As a typical literacy example related to the current study, we could mention the recent work done by Marusenko and Rodionova (2010), who suggested 51 potential features capable of distinguishing between two given authors (Molie`re vs. Corneille). These features were mainly structural (number of simple sentences, complex sentences, parenthesis phrases), or syntactic (number of conjugated verb forms, direct objects, subjects, subordinate clauses without a conjugated form of a verb, etc.).…”
Section: Related Workmentioning
confidence: 99%